Trauma surgery at a designated COVID-19-free site during the pandemic: a safe model and a possible way to restart routine elective surgery - Gonzi, Gianluca (Bone Jt Open, 2020)
AIMS: Elective operating was halted during the COVID-19 pandemic to increase the capacity to provide care to an unprecedented volume of critically unwell patients. During the pandemic, the orthopaedic department at the Aneurin Bevan University Health Board restructured the trauma service, relocating semi-urgent ambulatory trauma operating to the isolated clean elective centre (St. Woolos’ Hospital) from the main hospital receiving COVID-19 patients (Royal Gwent Hospital). This study presents our experience of providing semi-urgent trauma care in a COVID-19-free surgical unit as a safe way to treat trauma patients during the pandemic and a potential model for restarting an elective orthopaedic service. METHODS: All patients undergoing surgery during the COVID-19 pandemic at the orthopaedic surgical unit (OSU) in St. Woolos’ Hospital from 23 March 2020 to 24 April 2020 were included. All patients that were operated on had a telephone follow-up two weeks after surgery to assess if they had experienced COVID-19 symptoms or had been tested for COVID-19. The nature of admission, operative details, and patient demographics were obtained from the health board’s electronic record. Staff were assessed for sickness, self-isolation, and COVID-19 status. RESULTS: A total of 58 surgical procedures were undertaken at the OSU during the study period; 93% (n = 54) of patients completed the telephone follow-up. Open reduction and internal fixation of ankle and wrist fractures were the most common procedures. None of the patients nor members of their households had developed symptoms suggestive of COVID-19 or required testing. No staff members reported sick days or were advised by occupational health to undergo viral testing. CONCLUSION: This study provides optimism that orthopaedic patients planned for surgery can be protected from COVID-19 nosocomial transmission at separate COVID-19-free sites. Cite this article: Bone Joint Open 2020;1-6:302–308.